Analisis Pengaruh Pendapatan, Gini Rasio, dan Infrastruktur terhadap Indeks Pembangunan Manusia (IPM) di Indonesia - Suparlan Suparlan; Herawati Khotmi (ARZUSIN, 2025)
The limited scope of empirical studies on the determinants of the Human Development Index (HDI) in Indonesia serves as the background for this research, considering the strategic role of HDI as an indicator of societal welfare and quality of life. This study aims to evaluate the influence of per capita income, income inequality (Gini Ratio), and infrastructure development on Indonesia’s HDI during the 2014–2023 period. A quantitative approach was employed using a time series design, utilizing secondary data from the Central Statistics Agency and the Ministry of Finance of the Republic of Indonesia. The analysis was conducted using multiple linear regression, preceded by classical assumption testing, model feasibility testing, and both t and F statistical tests. The results indicate that per capita income and infrastructure development have a significant effect on HDI, while the Gini Ratio does not show a significant influence. These findings support human development theory, which emphasizes the importance of economic and infrastructure factors in improving quality of life. The study concludes that policies aimed at increasing income and advancing infrastructure development are key strategies in enhancing HDI in Indonesia. Theoretical and practical implications of this research include contributions to the human development literature and policy recommendations focused on strengthening economic dimensions and infrastructure equity.